Pt and TCO free hybrid bilayer silver nanowire-graphene counter electrode for dye-sensitized solar cells - Al-Mamun, Mohammad; Kim, Jae-Yup; Sung, Yung-Eun; Lee, Jae-Joon; Kim, Sung-Ryong (ELSEVIER SCIENCE BV, 2013)
Here we report a novel transparent conductive oxide (TCO) and Pt free silver nanowire and graphene nanoplatelet (AgNW-GNP) based hybrid counter electrode (CE) for dye-sensitized solar cells (DSSCs) having appreciable photovoltaic performances compared to reference Pt-FTO based DSSCs. Simple solution processed bilayer AgNW-GNP hybrid CEs were prepared to investigate its applicability in DSSCs based on their electrocatalytic and charge transport properties. DSSCs prepared with AgNW-GNP hybrid CEs containing the GNP loading of 0.88 mu g/cm(2) showed the photoconversion efficiency of 1.61 +/- 0.13% which is comparable with that of 1.87 +/- 0.15% made of standard Pt-FTO CEs. (C) 2013 Elsevier B. V. All rights reserved.